[ETS and scientific fraud strategies] (Tufts Archival Research Center, 2007)
Memorandum from Samuel D. Chicolte Jr. to Susan Stuntz with the supplement to the public smoking plan attached. Identifies the major goals of the program as addressing science fraud and environmental tobacco smoke. Lists several strategies to accomplish these goals as well as the goals and tactics associated with each strategy.